Seismicity in Strike‐Slip Foreland Faults (Central Betic Cordillera Front): Evidence of Indentation Tectonics - Tendero‐Salmerón, Víctor; Galindo‐Zaldivar, Jesus; Peláez, José A; Martínez‐Martos, Manuel; Henares, Jesús; Marín‐Lechado, Carlos; Gil, Antonio J.; López‐Garrido, Ángel Carlos (Tectonics, 2020)
Unexpected seismicity has been detected in the past few years along the northern Guadiana Menor River (Guadalquivir foreland basin) at the northern boundary of the Betic Cordillera. Earthquake focal mechanisms evidence the activity of N-S to NNE-SSW sinistral faults in the basement. Yet continuous GPS (CGPS) data show a westward movement in both the Prebetic Arc and the eastern Guadalquivir basin infill, which disagrees with the strike-slip faults. To more precisely describe the structure and evolution of the area, new Bouguer anomaly data from the southeastern basin combined with seismicity data, electric resistivity tomography profiles (ERT), and surface studies are provided. Given the soft consistency of the sedimentary infill in the area, surface evidence of faulting is scarce, limited to elongated channel and minor vertical faults affecting Quaternary sediments, where ERT profiles suggested the presence of faults. These results suggest that the Guadalquivir basin infill, the Prebetic Arc and the central Betic Cordillera move towards the west, independent from the Iberian crust, but indicating to some extent an upward propagation of the basement deformation. However, the basement is coupled with the Alboran Domain and undergoes NNW-SSE Eurasia-Nubia convergence and orthogonal extension. This scenario is suggestive of the initial stages of indentation tectonics, better developed in the eastern Betic Cordillera and the central Alboran Sea.
Keywords: foreland basin; gravity anomalies; seismic series; seismicity; strike-slip faults; Scopus; JCR